2023
DOI: 10.1038/s41588-023-01437-4
|View full text |Cite
|
Sign up to set email alerts
|

G4access identifies G-quadruplexes and their associations with open chromatin and imprinting control regions

Cyril Esnault,
Talha Magat,
Amal Zine El Aabidine
et al.

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 61 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…The presence of PQS was searched for detection thresholds above 1.2, 1.5, 1.8, and 2.0. PQS appearing at higher thresholds have a higher propensity to fold into G4s and form very stable structures . The raw data for all genomes analyzed are in Supporting Information 01, which also provides information on NCBI accession numbers, length, GC count, percentage GC genome content, and the number and frequency of PQS.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of PQS was searched for detection thresholds above 1.2, 1.5, 1.8, and 2.0. PQS appearing at higher thresholds have a higher propensity to fold into G4s and form very stable structures . The raw data for all genomes analyzed are in Supporting Information 01, which also provides information on NCBI accession numbers, length, GC count, percentage GC genome content, and the number and frequency of PQS.…”
Section: Methodsmentioning
confidence: 99%
“…Further, since G4 has been shown to cooperate with transcription factors at gene promoters 27,28 , we analyzed publicly available NGS data that were generated implementing different methods for the assessment of G4 formation (Figure 2i). On one hand, we analyzed ChIP-seq data that were generated using an artificial 6.7 kDa G4 probe (G4P) protein, which binds G4s with high affinity and specificity 24 .…”
Section: Mir-9 Is Required For H3k4me3 Broad Domains High Basal Trans...mentioning
confidence: 99%
“…On one hand, we analyzed ChIP-seq data that were generated using an artificial 6.7 kDa G4 probe (G4P) protein, which binds G4s with high affinity and specificity 24 . On the other hand, we analyzed NGS data that were generated by G4access, which is an antibody-independent method that relies on moderate nuclease digestion of chromatinized DNA 28 . Remarkably, we found by both approaches enrichment of G4 at the TSS of the miR-9 target gene (Figure 2i).…”
Section: Mir-9 Is Required For H3k4me3 Broad Domains High Basal Trans...mentioning
confidence: 99%
See 1 more Smart Citation
“…ComputaPonal studies have shown that G4s are not randomly distributed in the human genome; instead, they are concentrated in funcPonal regions such as promoters [9], telomeres [10], and intron-exon borders [11], suggesPng that G4s may have biological funcPons. Furthermore, in recent years, with the widespread applicaPon of single-molecule techniques in G4 research and the development of whole genome methods, including G4 ChIP-seq [12] and G4Access [13], more and more evidence indicates that G4s, parPcularly G4 secondary structures, are not genomic "junk" or accidents but possess important biological funcPons. Extensive studies have revealed that G4s are widely involved in the regulaPon of a variety of biological processes, including gene transcripPon [9], protein translaPon [14], genome stability [15], telomere regulaPon [16], and genome replicaPon [17].…”
Section: Introduc2onmentioning
confidence: 99%